PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS VIII SMP NEGERI 7 PADANG - Sari, Tasya Putri (Jurnal Edukasi dan Penelitian Matematika, 2023)
One of the skills that students must possess is the capacity for problem solving. Because students who study mathematics must be able to solve problems, this is the case. In reality, problem-solving abilities still need to be enhanced. This study aims to determine the impact of the Problem-Based Learning (PBL) paradigm on students' ability to solve mathematical problems. A pseudo-experiment with a Non Equivalent Posttest Only Control Group Design is used for this study. The research cohort was comprised of all eighth-grade pupils at SMP Negeri 7 Padang in TP 2022/23, as well as two sample classes. As a tool, the final exam was employed. The results of the hypothesis test obtained a P-value = 0.000 (α = 0.05), meaning that it rejects . The conclusion obtained is that the PBL model positively influences problem solving abilities.Keywords– Mathematical Problem Solving Ability, Problem Based Learning Model, Direct Learning Model